#### Answer

$-6i$

#### Work Step by Step

Combine like terms by factoring out $i$ to obtain:
$=i(-9+3)
\\=i(-6)
\\=-6i$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$-6i$

Combine like terms by factoring out $i$ to obtain:
$=i(-9+3)
\\=i(-6)
\\=-6i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.